Approaches to the Development of Endowment Funds in Russia as an Instrument of Mixed Financing of the Social Sphere - Chueva, Tatiana I.; Niyazova, Gulsina M.; Metsler, Andrey V.; Shkurkin, Dmitry V.; Aznabaeva, Gulmariam H.; Kim, Leonid I. (International Review of Management and Marketing, 2016)
In the context of budgetary constraints, the state educational institutions of vocational education are forced to seek investment resources to support their activities and compete with each other in the market, developing their competitive advantages. The article notes that one of the effective financial and economic institutions that ensure stability in financing producers of educational services is the endowment fund. Status of the Russian financial and economic system at the present stage of the global economic crisis, characterized by vague economic sphere, primitive and contradictory nature of the transformation processes, determines the need for reorganization of the systems and the management of financial resources of the enterprise. Significantly increases the importance of financial stability as a basic factor of their formation in the market and further development of interethnic value. Keywords: financial institutions, investment resources, investment funds JEL Classifications: G2; G31; H4